2016
DOI: 10.1586/14737175.2016.1158103
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of impulse control disorders in Parkinson’s disease: Practical considerations and future directions

Abstract: Impulse control disorders (ICDs) including compulsive gambling, buying, sexual behaviors, and eating occur relatively frequently in Parkinson disease (PD) with at least one ICD identified in 14% of PD patients in a large, multicenter, observational study. ICDs behaviors range widely in severity but can lead to catastrophic consequences, including financial ruin, divorce, loss of employment, and increased health risks. The main risk factor for ICDs in PD is the use of Dopamine agonists (DAs) and discontinuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…Dopaminergic approaches to treat ICD often fail because adjusting the dopaminergic medication dosage can prompt withdrawal symptoms or exacerbate motor and psychiatric symptoms (Ramirez-Zamora et al 2016). New treatments for ICD by modulating the serotonergic and noradrenergic, or possibly the opioid system, may circumvent this.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Dopaminergic approaches to treat ICD often fail because adjusting the dopaminergic medication dosage can prompt withdrawal symptoms or exacerbate motor and psychiatric symptoms (Ramirez-Zamora et al 2016). New treatments for ICD by modulating the serotonergic and noradrenergic, or possibly the opioid system, may circumvent this.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Patients and their relatives should be informed about the possibility of ICDs when levodopa or DAs are prescribed 46 . Clinicians should proactively investigate symptoms of impulsivity at each medical visit.…”
Section: Treatmentmentioning
confidence: 99%
“…Cognitive and executive dysfunction is prevalent in both disorders (Craig et al 2016; Goldman et al 2015). Impulse control disorders including compulsive gambling, shopping, sexual behaviors and eating occur relatively frequently in PD (Ramirez-Zamora et al 2016) and are often observed as an adverse reaction to PD treatment with dopaminergic drugs and deep brain stimulation of the subthalamic nucleus (for review, see Volkmann et al 2010). Dopamine (DA) has long been known to be a crucial modulator of striatal processing of cortical and thalamic signals, mediated through glutamatergic synapses on the principal striatal neurons (medium spiny).…”
Section: Introductionmentioning
confidence: 99%